Analisis Strategi Petani Kopi dalam Meningkatkan Pendapatan Menurut Perspektif Ekonomi Islam (Studi Kasus: Jorong Sungai Lambai Wonorejo Nagari Lubuk Gadang Selatan Kabupaten Solok Selatan) - Mega Noviani; Zulhelmi Zulhelmi (YASIN, 2026)
Although strategies to increase coffee farmers’ income have received attention in various studies, research that specifically discusses coffee farming strategies in a local context remains limited. This study aims to analyze the strategies employed by coffee farmers to increase their income and to identify the obstacles faced in developing coffee farming. This study used a qualitative approach with a case study design, involving 20 coffee farmers as informants selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the strategies implemented by coffee farmers to increase income included market development, product development, market penetration, integration, and diversification. The market development strategy was carried out through the expansion of marketing beyond the jorong area and the sale of coffee in the form of green beans at a higher selling price. The product development strategy was carried out through the selection of Arabica Ciari and Robusta coffee varieties and the processing of coffee from raw beans into powder. In addition, farmers also implemented market penetration, integration, and diversification strategies to increase added value and reduce economic risk. However, farmers still faced internal constraints in the form of limited capital, the not yet optimal implementation of post-harvest practices, and a lack of training and extension services, so that plantation management still depended on individual experience. External constraints included weather changes, pest and plant disease attacks, and fluctuations in coffee prices. This study concludes that the strategies implemented have contributed to increasing farmers’ income, but have not yet operated optimally due to various constraints. Therefore, the optimization of farming strategies and the enhancement of farmers’ capacity are important factors in improving the welfare of coffee farmers.